WHOLE BRAIN INTELLIGENCE (WBI) DURING THE TIME OF SIAM REVOLUTION IN 1688: IMPLICATIONS FOR COACHING SUCCESSION PLANNING MODEL - Soponkij, Udosak (Ph.D. in Social Sciences Journal, 2017)
No abstract available